2021
DOI: 10.14715/cmb/2021.67.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FOXA1 gene regulates the proliferation and invasion of human gastric cancer cells

Abstract: Forkhead box (FOX) transcription factors regulate the development of several human cancers. However, the role and therapeutic potential of FOXA1 in gastric cancer is still largely unexplored. The results showed a significant (P < 0.05) upregulation of FOXA1 in gastric cancer tissues and cell lines. Silencing of FOXA1 in gastric cells significantly (P < 0.05) decreased their viability through induction of apoptosis. The induction of apoptosis was associated with upregulation of Bax and downregulation of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Despite the fact that dysregulated expression of certain FOX genes has been observed in a few cancers, 30 , 31 the expression pattern of the entire FOX gene family across cancer types remains unclear. Filtering for cancer types with at least 10 matched tumor‐normal samples, 16 cancer types were selected for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that dysregulated expression of certain FOX genes has been observed in a few cancers, 30 , 31 the expression pattern of the entire FOX gene family across cancer types remains unclear. Filtering for cancer types with at least 10 matched tumor‐normal samples, 16 cancer types were selected for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Among all transcription factors regulating the three hub genes, FOXA1 with the highest NES (NES = 5.142) was considered as the most important transcription factors ( Figure 5C ). Existing studies have shown that the expression of FOXA1 affects the proliferation and invasion of gastric cancer cells ( Lin et al, 2018 ; Dai Y. et al, 2021 ). The result verified the objectivity of the three hub genes in gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The anti-apoptotic protein BCL-2 binds to mitochondria and prevents the release of cytochrome c from mitochondria into the cytoplasm. In contrast, the pro-apoptotic protein BAX translocalizes to mitochondria and increases mitochondrial membrane permeability, thereby initiating apoptosis [ [27] , [28] , [29] , [30] , [31] ]. Inhibition of the PI3K/AKT/mTOR signaling pathway and promotion of E-cadherin expression can inhibit the proliferation and invasion of pancreatic cancer cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%